Quintessential Affleck-Dine baryogenesis with non-minimal couplings - Bettoni, Dario; Rubio, Javier (Physics letters, 2018)
We present a novel Affleck–Dine scenario for the generation of the observed baryon asymmetry of the Universe based on the non-trivial interplay between quintessential inflationary models containing a kinetic dominated post-inflationary era and a non-minimally coupled U(1) field with a weakly broken B−L symmetry. The non-minimal coupling to gravity renders heavy the Affleck–Dine field during inflation and avoids the generation of isocurvature fluctuations. During the subsequent kinetic era the Ricci scalar changes sign and the effective mass term of the Affleck–Dine field becomes tachyonic. This allows the field to dynamically acquire a large expectation value. The symmetry of the Affleck–Dine potential is automatically restored at the onset of radiation domination, when the Ricci scalar approximately equals zero. This inverse phase transition results in the coherent oscillation of the scalar field around the origin of its effective potential. The rotation of the displaced Affleck–Dine field in the complex plane generates a non-zero B−L asymmetry which can be eventually converted into a baryon asymmetry via the usual transfer mechanisms.
Gesehen am 15.08.2019